OPTIMALISASI PELATIHAN KADER POSYANDU DAN GURU DALAM MENINGKATKAN PENDIDIKAN DAN KESEHATAN MASYARAKAT DESA MARGALUYU, JAWA BARAT - Sovitriana, Rilla; Budilaksono, Sularso; Dewi, Euis Puspita; Nasution, Evi Syafrida; Trikariastoto, ST; Nurina, Nurina; Kencana, Woro Harkandi (Universitas Mataram, 2024)
Margaluyu Village is one of the rural areas in West Java that still faces various challenges related to access to health and education services. Limited resources and infrastructure are the main obstacles in efforts to improve community welfare. Based on statistical data on the population according to occupation in Margaluyu village, the number of people who have not/don't work is around 3803, which is the largest number in the population data group based on occupation. From community service to increase the knowledge, skills and awareness of posyandu cadres and teachers in providing quality health services and effective learning to the people of Margaluyu Village, so that they can contribute to improving the welfare and quality of life of the community as a whole. Activities were carried out using training and discussion methods to increase the knowledge of posyandu cadres and teachers in Margaluyu village. The result is increased basic health knowledge and improved teaching skills thereby providing quality health services to the community and students. This training plan includes clear objectives, relevant material, interactive learning methods, and a structured implementation schedule. Conclusion: Conclusion: Posyandu cadre and teacher training has an important role in improving the health and education of the Margaluyu Village community. To continue to improve the quality and coverage of training programs, as well as expand collaboration with various related parties, such as educational institutions, health and village governments. So that a greater impact can be created in improving the health and education of the people of Margaluyu Village in a sustainable manner